Influence Good Corporate Governance, Capital Structure, and Company Size on Financial Performance of Oil and Gas Companies - Nuraini, Airin; Cahyadi, Ilhaamsyah Putra (Institut Bisnis dan Informatika Kesatuan, 2025)
The oil and gas sector is an important sector of the energy industry. This includes exploration, production, processing, distribution, sale of petroleum and natural gas. This sector has a crucial role in providing fuel for transportation, energy for households and industry, as well as raw materials for chemical products and other materials. Apart from that, this sector also plays a role in infrastructure and economic development in many countries that have abundant energy resources. The oil and gas industry will continue to grow, this is because oil and gas companies have energy resources that are important for the global economy This research was conducted to examine the influence of Good Corporate Governance, Capital Structure, and Company Size on Financial Performance. The sample used in this research is the financial reports of 12 oil and gas companies listed on the IDX for 2018-2022 using the purposive sampling method. The analytical method used is multiple linear regression analysis.The results of the research show that Good Corporate Governance and Company Size have no influence on Financial Performance, while Capital Structure has a significant influence on Financial Performance. Simultaneously GCG, DER, Company Size have a significant influence on the company's Financial Performance. Keywords : Good Corporate Governance, Debt to Equity Ratio, Firm Size, Financial Performance